CeO2NP priming enhances the seed vigor of alfalfa (Medicago sativa) under salt stress - Gao, Jinzhu; Liu, Yanzhi; Zhao, Donghao; Ding, Yanzhi; Gao, Le; Su, Xihao; Song, Kexiao; He, Xueqing (Frontiers in Plant Science, 2024)
Soil salinization is a common environmental problem that seriously threatens crop yield and food security, especially through its impact on seed germination. Nanoparticle priming, an emerging seed treatment method, is receiving increasing attention in improving crop yield and stress resistance. This study used alfalfa seeds as materials to explore the potential benefits of cerium oxide nanoparticle (CeO2NP) priming to promote seed germination and improve salt tolerance. CeO2NPs at concentrations up to 500 mg/L were able to significantly alleviate salt stress in alfalfa seeds (200 mM), with 50 mg/L of CeO2NP having the best effect, significantly (P< 0.05) increasing germination potential (from 4.0% to 51.3%), germination rate (from 10.0% to 62.7%), root length (from 8.3 cm to 23.1 cm), and seedling length (from 9.8 cm to 13.7 cm). Priming treatment significantly (P< 0.05) increased seed water absorption by removing seed hardness and also reducing abscisic acid and jasmonic acid contents to relieve seed dormancy. CeO2NP priming increased α-amylase activity and osmoregulatory substance level, decreased reactive oxygen species and malonaldehyde contents and relative conductivity, and increased catalase enzyme activity. Seed priming regulated carotenoid, zeatin, and plant hormone signal transduction pathways, among other metabolic pathways, while CeO2NP priming additionally promoted the enrichment of α-linolenic acid and diterpenoid hormone metabolic pathways under salt stress. In addition, CeO2NPs enhanced α-amylase activity (by 6.55%) in vitro. The optimal tested concentration (50 mg/L) of CeO2NPs was able to improve the seed vigor, enhance the activity of α-amylase, regulate the osmotic level and endogenous hormone levels, and improve the salt tolerance of alfalfa seeds. This study demonstrates the efficacy of a simple seed treatment strategy that can improve crop stress resistance, which is of great importance for reducing agricultural costs and promoting sustainable agricultural development.